COMPARATIVE ASSESSMENT OF MOLECULAR AND IMMUNOHYSTOCHEMICAL MARKERS OF IMMUNE ENDOTHELIAL DAMAGE IN PREGNANTS WITH ARTERIAL HYPERTENSION AND PREECLAMSIA - I. S. Sidorova; A. L. Unanayan; N. A. Nikitina; A. A. Rzaeva; V. V. Kinyakin (Акушерство, гинекология и репродукция)
Prospective examination of 21 pregnant women with chronic arterial hypertension, 81 pregnant women with preeclamsia of various degree of severity and 25 healthy pregnant women was conducted. Comparative assessment of neurospecific proteins NSE and GFAP in blood serum and also immunomorphologic investigation of placenta tissue in women with hypertension and preeclampsia was demonstrated. Compared to blood serum and placenta tissue taken from women with preeclamsia, in women with arterial hypertension neurospecific proteins with high immunogenic activity that may lead to development of severe immunopathologic process were not discovered. Pregnancy prolongation with adequate hypotensive therapy and good blood pressure control is possible. Development of preeclampsia is associated with sudden increase in neurospecific protein levels, severe immune endothelial damage of macro-and microcirculation vessels; To stop the progression of this process is possible only with delivery, that is indicated in case of eclampsia, severe preeclampsia and in its moderate forms ineffective treatment.